Keys to Recruiting and Retaining Seriously Ill African Americans With Sickle Cell Disease in Longitudinal Studies: Respectful Engagement and Persistence. (February 2020) - Suarez, Marie L.; Schlaeger, Judith M.; Angulo, Veronica; Shuey, David A.; Carrasco, Jesus; Roach, Keesha L.; Ezenwa, Miriam O.; Yao, Yingwei; Wang, Zaijie Jim; Molokie, Robert E.; Wilkie, Diana J.
Objectives: Sickle cell disease (SCD) is a serious illness with disabling acute and chronic pain that needs better therapies, but insufficient patient participation in research is a major impediment to advancing SCD pain management. The purpose of this article is to discuss the challenges of conducting an SCD study and approaches to successfully overcoming those challenges. Design: In a repeated-measures, longitudinal study designed to characterize SCD pain phenotypes, we recruited 311 adults of African ancestry. Adults with SCD completed 4 study visits 6 months apart, and age- and gender-matched healthy controls completed 1 visit. Results: We recruited and completed measures on 186 patients with SCD and 125 healthy controls. We retained 151 patients with SCD with data at 4 time points over 18 months and 125 healthy controls (1 time point) but encountered many challenges in recruitment and study visit completion. Enrollment delays often arose from patients' difficulty in taking time from their complicated lives and frequent pain episodes. Once scheduled, participants with SCD cancelled 49% of visits often because of pain; controls canceled 30% of their scheduled visits. To facilitate recruitment and retention, we implemented a number of strategies that were invaluable in our success. Conclusion: Patients' struggles with illness, chronic pain, and their life situations resulted in many challenges to recruitment and completion of study visits. Important to overcoming challenges was gaining the trust of patients with SCD and a participant-centered approach. Early identification of potential problems allowed strategies to be instituted proactively, leading to success.